PEMIKIRAN AL-GHAZALI TENTANG SOSOK GURU PROFESIONAL YANG IDEAL - Rodhiah, Saniatur; Wardan, Khusnul (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
In Islamic perspective, a teacher is not merely a transmitter of knowledge but also a moral educator and spiritual guide who plays a crucial role in shaping students’ character. AlGhazali’s thoughts on the concept of the ideal teacher remain highly relevant to the discourse on teacher professionalism in the modern era. This article focuses on analyzing Al-Ghazali’s perspective regarding the characteristics of an ideal professional teacher, particularly in terms of spiritual, moral, and intellectual competence. This study employs a qualitative method with a library research approach, examining Al-Ghazali’s works especially Ihya’ Ulum al-Din and supported by relevant secondary sources. The research stages include identifying the basic concepts of teacherhood according to Al-Ghazali, analyzing Islamic educational principles, and interpreting their relevance to today’s professional teacher standards. The findings indicate that the ideal teacher, according to Al-Ghazali, is not only one who masters knowledge comprehensively but also embodies noble character, sincerity, humility, and serves as a role model for students. Moreover, the teacher must be able to provide spiritual guidance so that the transfer of knowledge does not remain at the cognitive level but also shapes personality and strengthens students’ relationship with God. The main conclusion emphasizes that the concept of an ideal professional teacher in Al-Ghazali’s perspective integrates academic competence with moral and spiritual dimensions, making it highly relevant as a reference for developing teacher professionalism in today’s era of ethical and social challenges. ABSTRAKGuru dalam pandangan Islam bukan sekedar penyampai ilmu pengetahuan, tetapi juga pendidik akhlak dan pembimbing spiritual yang berperan membentuk kepribadian peserta didik. Pemikiran Al-Ghazali mengenai sosok guru ideal masih relevan untuk dikaji dalam konteks profesionalisme guru di era modern. Artikel ini berfokus pada analisis pemikiran Al-Ghazali tentenag kriteria guru profesional yang ideal, khususnya terkait kompetensi spiritual, moral, dan intelektual. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kepustakaan (library research) melalui telaah kritis terhadap karya-karya Al-Ghazali, terutama Ihya’ Ulum al-Din dan literatur sekunder yang relevan. Langkah penelitian meliputi identifikasi konsep dasar guru menurut Al-Ghazali, analisis prinsip-psinsip pendidikan Islam, serta interpretasi relevensinya dengan standar profesional guru masa kini. Hasil kajian menunjukkan bahwa guru ideal menurut Al-Ghazali bukan hanya menguasai ilmu secara mendalam, tetapi juga berakhlak mulia, ikhlas, tawadhu’, serta menjadikan dirinya teladan bagi peserta didik. Selain itu, guru harus mampu membimbing secara spiritual agar ilmu yang ditransfer tidak sekadar bersifat kognitif, tetapi juga membentuk kepribadian dan mendekatkan murid kepada Allah. Simpulan utama penelitian ini menegaskan bahwa konsep guru profesional ideal dalam perspektif Al-Ghazali tifak hanya mencakup aspek kompetensi akademik, tetapi juga dimensi moral dan spiritual, sehingga relevan dijadikan rujukan dalam membangun karakter guru di era modern yang sarat tantangan etis dan sosial.